1998
DOI: 10.1097/00004728-199803000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Tibial Stress Fractures: A Report of Eight Cases and Review of the Literature

Abstract: Longitudinal stress fractures have characteristic imaging features, and familiarity with these features is necessary for timely and efficient diagnosis, avoiding morbidity due to delay or use of unnecessary tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…To our knowledge, however, no previous study in which CT and MR imaging findings were evaluated in patients with early stress injuries exists in the literature (2,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, however, no previous study in which CT and MR imaging findings were evaluated in patients with early stress injuries exists in the literature (2,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…However, CT was used to depict more lesions than did MR imaging (Table 4). MR imaging allows depiction of periosteal and endosteal marrow edema, which are believed to be useful ancillary markers for stress injury (10,19,37). Both T2-weighted images and STIR images are reliable in revealing the presence of cortical stress injury.…”
Section: Discussionmentioning
confidence: 99%
“…In the original description of this entity [10], five of the six cases involved the tibia; the sixth case involved the femur. There have since been numerous additional reports of longitudinal stress fractures involving the tibia or femur [7,8,11,12,19,20,22,23]. To our knowledge, this is the first reported case of a longitudinal stress fracture occurring in the upper extremity.…”
Section: Discussionmentioning
confidence: 65%
“…48 The poor sensitivity related to early bony changes associated with stress fracture results in films being read as normal for up to 1 to 3 weeks following the onset of pain complaints. 8,17,47,54 Our patient's initial hip films were taken within this 1-to 3-week window where films may miss a stress fracture. Bone scintigraphy (scan) is often ordered when osseous lesions, such as stress fractures, are suspected because of the high sensitivity in detecting early bony changes 22,41,43,47 and abnormalities within 6 to 72 hours post onset of pain complaints.…”
Section: Discussionmentioning
confidence: 99%
“…However, making a specific diagnosis is often impossible based on bone scan alone due to poor specificity. 47,54 This lack of specificity was demonstrated by Shin et al, 55 who found that, when evaluating 22 patients with hip pain, scintigraphy had an accuracy of 68% (32% false positives) in diagnosis of femoral neck stress fractures, compared to 100% accuracy for MRI. MRI is considered by many to be the gold standard for diagnosing stress fractures, depicting a decreased (low) signal intensity of the fracture line on T1 weighted images and an increased (high) signal intensity in T2 weighted images.…”
Section: Discussionmentioning
confidence: 99%